The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1023/a:1022913015916
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The contamination of cell cultures by mycoplasmas remains a major problem in cell culture. Mycoplasmas can produce a virtually unlimited variety of effects in the cultures they infect. These organisms are resistant to most antibiotics commonly employed in cell cultures. Here we provide a concise overview of the current knowledge on: (1) the incidence and sources of mycoplasma contamination in cell cultures, the mycoplasma species most commonly detected in cell cultures, and the effects of mycoplasmas on the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
190
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 263 publications
(199 citation statements)
references
References 20 publications
2
190
0
5
Order By: Relevance
“…More specifically, the cell products could be contaminated by a number of microorganisms like bacteria (including Mycoplasma), yeast, and fungi [1]. Of these, Mycoplasma is considered as one of the major threats for cell cultures [2,3]. A recent study reported a 19% contamination rate by Mycoplasma species and the rate increased to 22% if the mixed contamination is taken into account, in which Mycoplasma is the main isolate [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the cell products could be contaminated by a number of microorganisms like bacteria (including Mycoplasma), yeast, and fungi [1]. Of these, Mycoplasma is considered as one of the major threats for cell cultures [2,3]. A recent study reported a 19% contamination rate by Mycoplasma species and the rate increased to 22% if the mixed contamination is taken into account, in which Mycoplasma is the main isolate [4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a 19% contamination rate by Mycoplasma species and the rate increased to 22% if the mixed contamination is taken into account, in which Mycoplasma is the main isolate [4]. Thus, Mycoplasma contamination can interfere with a number of biological parameters and influence the final data during routine cultivation or experimental investigation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent contaminant mycoplasmas of cell cultures are the human M. orale, M. fermentans, M. hominis, the bovine M. arginini, and the porcine species M. hyorhinis, indicating that the sources for mycoplasma contaminations in cell culture are mainly laboratory personnel, contaminated serum or reagents and other contaminated cell cultures Uphoff and Drexler 2002). Mycoplasmas affect several cell parameters including growth, morphology, metabolism, antigenicity and the genome of the cultured cells (Razin et al 1998;Drexler and Uphoff 2002;Rottem 2003) without inducing overt visual changes.…”
Section: Introductionmentioning
confidence: 99%
“…Die US-amerikanische Food and Drug Administration (FDA) und die DSMZ führen daher eine Reihe von Verfahren für den Nachweis dieser Kontaminationen an, von denen die Polymerase-Kettenreaktion (polymerase chain reaction, PCR) die am weitesten verbreitete ist. [9,10] Für das verschließende Oligonukleotid wurde nun eine Sequenz ausgewählt, die im Mycoplasma-Genom konserviert ist und zu einem Fragment der 16S-ribosomalen RNA-Untereinheit korrespondiert (O1, 5'-GGG AGC AAA CAG GAT TAG ATA CCC T-3'). [12,13] Die mesoporçsen MCM-41-Nanopartikel wurden nach bekannten Vorschriften hergestellt.…”
Section: In Memoriam Enrique Pørez-payµunclassified